Evaluasi Pendidikan Jarak Jauh Mata Kuliah Flight Plan Program Studi Lalu Lintas Udara - Endang Sugih Arti; Lina Rosmayanti (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
This study aims to determine the results of the implementation of distance learning for the online Flight plan course due to the impact of the COVID-19 pandemic. This research uses descriptive quantitative method and data collection uses a questionnaire method and secondary data is used to evaluate Distance Learning (PJJ). In this study more focused on Kirkpatrick's Evaluation Model. Four levels of Kirkpatrick's Evaluation Model, each was assessed with a different assessment tool. The sample in this study were cadets of the Air Traffic DIV Study Program totaling 48 people. Reaction Evaluation (Evaluating Reaction) is carried out by using a reaction sheet in the form of a questionnaire so that it is easier and more effective to measure cadets' satisfaction with the Flight Plan course learning activities. Learning evaluation is carried out through an assessment of the learning process, using a quiz assessment rubric 2 (two) times at the beginning and at the end of the final exam. Behavioral evaluation is carried out by assessing the ability of air traffic competency practice in implementing the flight plan concept. Evaluating results are related to the final results of cadets, namely the final semester test scores. The results of the study describe the Kirkpatrick Evaluation Model in the Flight Plan Subject Learning Program which is declared effective in learning theory, but when entering into practice, it is difficult to use the flight plan data processing system which is currently not available as a practice media for online flight plan courses.